Innovative Learning Design Assisted by Comic Media in Social Studies - Hilmiah, Anis Syatul (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2025)
Learning innovation in social studies learning is important, especially for designing learning. This study aims to examine the effectiveness and relevance of comic media as a tool for developing social studies learning. This study uses a literature study method by analyzing various indexed and accredited journals that highlight the use of comics in social studies learning. The results indicate that comics in addition increase students' interest in learning but also help in understanding complex concepts through visualization. Comic media, when combined with innovative learning strategies, can have a positive impact on student learning outcomes in social studies learning.